theory and practice - "Ozbilgin, Mustafa" (New York, 2005)
Contents: Introducing international human resource management / Mustafa Ozbilgin -- Aspects of international human resource management / Mustafa Ozbilgin -- The global workforce / Mine Karatas-Ozkan -- Human resource management in an international context / Zeynep Girgin -- National context of international human resource management / Moira Calveley -- Strategic aspects of international human resource management / Ahu Tatli -- Operational aspects of international human resource management / Olympia Kyriakidou -- International careers / Yehuda Baruch -- Competencies of international human resource managers / Moira Calveley -- Challenges facing international human resource management / Mustafa Ozbilgin.
includes bibliography and index
Keywords: International business enterprises--Personnel management; International human resource management